An effective numerical modelling strategy for FRCM strengthened curved masonry structures. (1st January 2023) - Castellano, Anna; Fraddosio, Aguinaldo; Oliveira, Daniel V.; Piccioni, Mario D.; Ricci, Eleonora; Sacco, Elio
Highlights: A new numerical modeling strategy for FRCM strengthened curved masonry structures. High accuracy combined with low computational costs. A small number of mechanical parameters is needed, easy to experimentally determine. Large sensitivity analysis on the effect of variations of mechanical parameters. Application to the evaluation of the seismic capacity of an FRCM reinforced vault. Abstract: Fabric Reinforced Cementitious Matrix (FRCM) composites are currently considered a very effective solution for strengthening masonry constructions. However, the mechanical interactions governing the response and the strength of FRCM reinforced masonry structures are very complex, especially in the case of curved structures. Moreover, these interactions involve several interfaces between different materials. Thus, the development of accurate numerical models for curved FRCM reinforced masonry structures comes up against several difficulties, and models too complex for practical applications can be obtained. In addition, several mechanical parameters needed for the calculations are generally inaccessible by conventional experimental tests. Here, a suitable numerical modelling strategy for FRCM strengthened curved masonry structures is proposed to combine the accuracy in simulating the actual behaviour in terms of stiffness, strength and collapse mechanisms with a reasonable simplicity, making the proposed approach usable also by practitioners, by adopting commercial codes and at a moderate computational effort. The relatively small number of mechanical parameters characterizing the model can be determined by ordinary experimental tests on materials or by literature formulations. The proposed modelling strategy is validated with respect to experimental data found in literature concerning a FRCM reinforced masonry barrel vault, and then is employed for studying the seismic capacity of the vault through a pushover analysis. A broad sensitivity analysis sheds light on the effect of variations of the mechanical parameters on the predicted overall behaviour, showing the robustness of the results obtainable through the proposed approach concerning inaccuracies in the determination of the parameters often very difficult to determine by ordinary experimental tests on masonry structures.